ALIH TEKNOLOGI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS DAN PROFITABILITAS USAHA RUMAHAN “NAURAH CAKES” - Adhe Anggry; Shanty Dwi Krisnaningsih (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
Home businesses are part of UMKM whose existence is very useful in improving the national economy, one of which is in the distribution of the people's income. This science and technology for society (IbM) activity targets home business called "Naurah Cakes". This home business located in Pangkalbalam sub-district, Pangkalpinang city is engaged in the cake and bread business with the main product being birthday cake which has been occupied since 2010. The problems faced by partners are 1) lack of capital, 2) lack of equipment 3) limited human resources, and 4) the absence of financial statements. This IbM activity aims to increase productivity and profitability through technology transfer in the form of stand mixers, frosting deco pens, printers, and cork cutters for the process of making and decorating birthday cakes. The methods used in this IbM activity include training, mentoring, and monitoring. The results of this IbM activity are as follows: 1) an increase in productivity seen from the aspect of effectiveness in the process of making birthday cakes, 2) an increase in the quality of the birthday cake produced and 3) an increase in profitability by 19.44% from 40.47% before the activity. to 54.91% at the end of the activity. Home Business "Naurah Cakes" is a very productive and creative IbM partner, but it needs to be supported by more modern science and technology and sustainable assistance so that the business can develop better, so that in the future partners can increase their turnover, quality, and quantity of their business.